PENDEKATAN DEEP LEARNING PADA PEMBELAJARAN IPA DI SEKOLAH DASAR NEGERI 58 MOJO SRAGEN - Septyana Candra Puspita; Sri Wardani; Adinda Nova Permatasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the application of the deep learning approach in science learning at SDN 58 Mojo Sragen. The deep learning approach focuses on three aspects, namely meaningful, mindful and joyful, which is in line with the direction of the Merdeka Curriculum philosophy which prioritizes learning that is adapted to students' needs, flexible and contextual. This research is based on observation data, interviews and documentation, then analyzed through data reduction, data presentation and drawing conclusions. The data analysis technique used is descriptive qualitative with research subjects being teachers and students. The research results show that the application of deep learning is able to increase student involvement to realize student center learning, deepen science concepts, and is able to encourage the formation of high-level thinking skills. Teachers have an important role in facilitating a student-centered learning process through exploratory studies and contextual problem solving. This research recommends that during the learning process at least one form of technology integration be inserted so that learning includes deep learning elements, namely mindfulness, meaning and joyful.